IN PURSUIT OF SUSTAINABILITY: TOWARDS SUSTAINABLE FUTURE THROUGH EDUCATION (International Journal of Innovative Technologies in Economy, 2022)
Higher Education Institutions increasingly include sustainable development concepts in their programs to teach their students about sustainability. This tendency is encouraged by the Sustainable Development Goals. Today’s technological age implies concerns about sustainability including ethical decision-making and responsible behavior of organizations and leaders. Moreover, the Covid-19 pandemic impacted sustainable development and highlighted the need for a more sustainable future. Sustainability can positively change value culture, the environment, and improve the quality of life. Although incorporating sustainability into the curriculum creates challenges for universities, it can also offer opportunities for educational institutions. Universities have an important role to play in the transition towards sustainability. They must not only incorporate the concept into research and teaching but also implement it on campus. This review article provides a brief overview of sustainable development in higher education institutions and discusses how universities adopt and apply sustainability principles. It also explores how sustainability can be integrated into various disciplines and sheds light on students’ and academics’ attitudes toward Education for Sustainability.